The Influence of Good Corporate Governance Mechanisms, Gender Diversity, and Profitability on Financial Distress - Rohmawati, Indah; Utami, Wiwik (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
This study aims to analyze the influence of Good Corporate Governance (GCG) mechanisms, gender diversity, and profitability on financial distress in manufacturing companies in the consumer non-cyclicals sector listed on the Indonesian Stock Exchange during a specified period. Financial distress is a critical condition that can threaten a company's operational continuity. The methodology employed is logistic regression analysis with a sample of companies that meet certain criteria, resulting in a comprehensive dataset. The findings indicate that institutional ownership and audit committees do not have a significant impact on financial distress, while gender diversity also shows no meaningful effect. Conversely, net profit margin is found to negatively influence financial distress, indicating that companies with lower net profit margins are more vulnerable to financial difficulties. The developed regression model demonstrates substantial explanatory power regarding the variation in interest coverage ratios based on the independent variables studied. This research provides important insights for companies and stakeholders in implementing good governance practices and considering gender diversity as a factor in financial risk management. The findings are expected to contribute to the development of theory and practice in accounting and financial management, as well as assist companies in preventing financial distress and enhancing long-term performance.